Pemberdayaan Difabel dengan Pemanfaatan Limbah Kain Perca Menjadi Produk Bernilai Ekonomi - Rahayu, Devi Budi; Solihin, Didin; Nahtip, Annajmi; Amalia, Nok; Fadhilah, Nurfani; Nurilmi, Rizta Izza; Sukmawati (Profetik: Jurnal Pengabdian Masyarakat, 2023)
Most of the people of Bawah Banjaran Village have businesses in the convection industry. This causes an abundance of patchwork waste. However, this waste cannot be utilized optimally. In the southern part of Batas Banjaran Village there is the Tegal Regency Loka Bina Karya (LBK) office. LBK is an institution under the auspices of the Tegal Regency Social Service. This institution is tasked with protecting, protecting and providing training for people with disabilities in Tegal Regency. People with disabilities are people who need special attention from the government or non-governmental organizations so that they can live a good and decent life. So far, some people have often viewed people with disabilities as people who are unable to live their lives independently, they are often ostracized and even discriminated against. To solve this problem, we KKN Group 7 students held training on making patchwork waste crafts. This training aims to ensure that people with disabilities have skills that are appropriate to their limitations so that they can increase their sense of self-confidence and independence in living their daily lives.